How Do Masters of Public Health Programs Teach Monitoring and Evaluation? - Negandhi, Himanshu; Negandhi, Preeti; Zodpey, Sanjay P.; Kulatilaka, Hemali; Dayal, Radhika; Hart, Lauren J.; Grewe, Marybeth (Frontiers in Public Health, 2017)
Introduction The health systems in developing countries face challenges because of deficient monitoring and evaluation (M&E) capacity with respect to their knowledge, skills, and practices. Strengthening M&E training in public health education can help overcome the gaps in M&E capacity. There is a need to advance the teaching of M&E as a core element of public health education. Objectives To review M&E teaching across Masters of Public Health programs and to identify core competencies for M&E teaching in South Asian context. Materials and methods We undertook two activities to understand the M&E teaching across masters level programs: (1) desk review of M&E curriculum and teaching in masters programs globally and (2) review of M&E teaching across 10 institutions representing 4 South Asian countries. Subsequently, we used the findings of these two activities as inputs to identify core competencies for an M&E module through a consultative meeting with the 10 South Asian universities. Results Masters programs are being offered globally in 321 universities of which 88 offered a Masters in Public Health, and M&E was taught in 95 universities. M&E was taught as a part of another module in 49 institutions. The most common duration of M&E teaching was 4–5 weeks. From the 70 institutes where information on electives was available, M&E was a core module/part of a core module at 42 universities and an elective at 28 universities. The consultative meeting identified 10 core competencies and draft learning objectives for M&E teaching in masters programs in South Asia. Conclusion The desk review showed similarities in M&E course content but variations in course structure and delivery. The core competencies identified during the consultation included basic M&E concepts. The results of the review and the core competencies identified at the consultation are useful resources for institutions interested in refining/updating M&E curricula in their postgraduate degree programs. Our approach for curriculum development as well as the consensus building experience could also be adapted for use in other situations.